PELATIHAN MICROSOFT OFFICE PADA PEGAWAI KANTOR KPU MEDAN - Kamson Sirait; Jonas Franky R. Panggabean; Leliana Harahap; Jontinus Manullang; Sartika Dewi Purba; Bena Br. Ginting (Universitas Methodist Indonesia, 2021)
The development of information technology does not only play a role in the economic field, but also in the field of education. Today every employee at almost all levels of education is required to be technology literate, especially information technology. In addition to supporting educational activities, information technology literacy also supports teachers in solving administrative problems. Some of the software that can be used to support education and administrative issues are Microsoft Word, Microsoft Excel, and Microsoft PowerPoint. Microsoft Word, Microsoft Excel, and Microsoft PowerPoint software have many features that some users are still not familiar with. This is experienced by the Medan KPU Office employees who are not familiar with the tools that are widely provided in Microsoft Word, Microsoft Excel, and Microsoft PowerPoint software. Some of the obstacles that are often encountered are the less than optimal use of the merge function in Word, the function of conditional formulas in Excel and animation, and multimedia in PowerPoint. This is the background for the dedicated team to provide training on